New approaches for cooling photovoltaic/thermal (PV/T) systems - Bouzoukas, Asterios (2008)
Today the majority of UK's energy needs are met by fossil fuels. An energy sector that uses 30% of this energy and generates 28% of the total emissions is domestic sector. To reduce the emissions generated by fossil fuels UK government decided to increase the energy coming from renewable sources by 2020. A renewable energy that can contribute is solar energy. Solar thermal collectors and photovoltaics are two means of transforming solar energy to thermal and electrical energy.